Zeitschrift für Unternehmensgeschichte : Journal of Business History (De Gruyter Oldenbourg, 2017)
The Journal of Business History addresses all facets of business history, taking a broad approach that encompasses neighboring disciplines, international developments, and an expanded definition of the firm. In order to publish first-class research that actively engages with companies, the economy, and the political sector, the journal solicits contributions from promising authors around the globe. Articles are accepted in German or English.